Knowledge of nursing students about prevention of radiodermatitis - Guerra, Gerlaine Rodrigues; Souza, Lia Raquel Monturil Vaz de; Reis, Paula Elaine Diniz dos; Faustino, Andréa Mathes (Revista de enfermagem UFPE on line, 2009)
ABSTRACTObjective: to assess the knowledge of the last semester of the undergraduate nursing course students on prevention of radiodermatitis. Methods: this is about a cross-sectional study, from survey type. For data collection was applied a questionnaire for students of the 8th semester nursing course in four universities in Brasilia city. Statistical analysis was performed using the Statistical Package for Social Science, version 13.0. This study has been approved by the Committee of Ethics in Research of UNIEURO University Center (010/2008). Results: in a research with 52 students, of which have 44% reported the approach of cancer in some subjects during the course. When asked about the knowledge of prevention and treatment of radiodermatitis, except by students of the institution A, there was a good level of knowledge about the possible nursing interventions. Conclusion: the results suggest that the academics did not have sufficient knowledge of prevention of radiodermatitis caused by ionizing radiation in the treatment with radiotherapy. The training of nurses to prevent and treat the toxicities associated to cancer therapeutic modalities, especially in the study of radiodermatitis, which is more than essential, and the building up of this knowledge should start in the undergraduate course. Descriptors: cancer; radiotherapy; nursing care. RESUMOObjetivo: verificar o conhecimento de alunos do último semestre do curso de graduação em enfermagem sobre prevenção de radiodermatite. Métodos: trata-se de estudo seccional, tipo survey. Para a coleta de dados foi usado questionário aplicado aos alunos do 8º semestre do curso de enfermagem em quatro universidades de Brasília, após aprovação pelo Comitê de Ética em Pesquisa do Centro Universitário UNIEURO (010/2008). A análise estatística foi realizada com auxílio do Statistical Package for Social Science, versão 13.0. Resultados: participaram da pesquisa 52 estudantes, dos quais 44% referiram abordagem da oncologia em alguma disciplina no decorrer do curso. Quando questionados acerca do conhecimento sobre prevenção e tratamento da radiodermatite, exceto pelos alunos da instituição A, não houve bom nível de conhecimento sobre as possíveis intervenções de enfermagem. Conclusão: os resultados sugerem que os acadêmicos não possuíam conhecimento suficiente sobre prevenção de radiodermatite causada pela radiação ionizante no tratamento com radioterapia. Assim, a capacitação do enfermeiro para prevenir e tratar as toxicidades inerentes às modalidades terapêuticas oncológicas, destacando-se neste estudo a radiodermatite, é imprescindível, devendo a construção desse conhecimento iniciar ainda na graduação. Descritores: câncer; radioterapia; cuidados de enfermagem. RESUMENObjetivo: evaluar los conocimientos de los estudiantes del último semestre de la Escuela Universitaria de Enfermería en la prevención de Radiodermatitis. Métodos: es uma investigación transversal, tipo survey, por medio de un cuestionario aplicado a los estudiantes del 8º semestre del curso de enfermería en cuatro universidades de la ciudad de Brasilia. Este estúdio fue aprobado por el Comité de Ética em Investigación del Centro Universitario UNIEURO (010/2008). El análisis estadístico se realizó utilizando el Statistical Package for Social Science, version 13.0. Resultados: una búsqueda de 52 estudiantes, 44% informó obtener alguna informacion sobre el cáncer en algunas clase durante el curso de enfermeria. Cuando se les preguntó por el conocimiento sobre la prevención y el tratamiento de Radiodermatitis salvo por los estudiantes de la institución A, hubo buen nivel de conocimiento acerca de las posibles intervenciones de enfermería. Conclusión: los resultados sugieren que los académicos no tienen conocimientos suficientes sobre la prevención de Radiodermatitis causados por las radiaciones ionizantes en el tratamiento con radioterapia, por lo que la formación del personal de enfermería para prevenir y tratar la toxicidad asociada al cáncer de modalidades terapéuticas, especialmente en el estudio Radiodermatitis es esencial, y la construcción de este conocimiento debe iniciar en la graduación. Descriptores: cáncer; radioterapia; atención de enfermería.